The technical and financial feasibility analysis of art paper production from betel nut husk fibre and paper waste - Azimmatul Ihwah; Ika Atsari Dewi; Hendrix Yulis Setyawan; Erina Permata Puteri Yuscandra (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Art paper made of betel nut husk fibre and paper waste is one example of an innovative product. Therefore, an analysis of the technical and financial feasibility of this innovation needed to be conducted. This research aimed to determine the technical and financial feasibility of the production business of art paper from betel nut husk fibre and paper waste. The technical aspect will focus on the technology utilized, primary raw material and additional raw material, production capacity, and any workforce involved in the business. Meanwhile, the financial aspect will emphasize the calculation of the Main Production Cost (MPC), Break Even Point (BEP), Business Efficiency (R/C Ratio), Payback Period (PP), Net Present Value (NPV), and Internal Rate of Return (IRR). The calculation result of the feasibility analysis shows that Production Cost (HPP) is IDR 12,786.00, BEPunit is 9,271 paper sheet, BEP (IDR) is IDR 148,326,906.00, R/C Ratio is 1.56, PP will be for 2.2 years, NPV is IDR 2,078,713,958.00, and IRR is 68.36%. Based on this result, this business on betel nut husk fibre and paper-based waste art paper is considered worth running.